Time Point, Etiology, and Short-Term Outcome of Repeated Mechanical Thrombectomy Due to Recurrent Large Vessel Occlusion - Weber, Ralph; Stracke, Paul; Chapot, René (Frontiers in Neurology, 2019)
Background: Data on time point and etiology of repeated stroke caused by large brain vessel occlusion (LVO) resulting in repeated mechanical thrombectomy (MT) in acute stroke patients is very limited. Methods: We retrospectively reviewed all acute stroke patients treated with MT with stent retrievers or aspiration systems between January 2010 and June 2018 to identify patients who received two or more MT treatments due to recurrent LVO in our tertiary neurovascular center. Short-term outcome was assessed using the NIH stroke scale score at discharge. Results: We identified 35 out of 2470 acute stroke patients treated with MT who had recurrent LVO and received repeated MT. Mean age at first MT was 69.3 (± 15.8) years and the mean time interval between the first and second MT was 147 (± 241) days, and 8 patients experienced short-term LVO recurrence within 3 days. Fifteen (43%) patients had cardioembolic, 9 (26%) arterioembolic, 4 (11%) mixed cardio-/arterioembolic, and 7 (20%) patients had unknown stroke etiology. Patients with cardioembolic stroke were substantially older, had no or insufficient oral anticoagulation at the time of the first and repeated LVO, and repeated LVO occurred very early in 50%. Seventeen (49%) patients had a NIHSS score of 0 or 1 at discharge and seven (20%) patients died in the hospital after repeated MT. No bleeding complications occurred. Conclusions: Repeated MT due to recurrent LVO is a rarely performed, safe, and effective procedure in acute stroke patients. Missing or insufficient anticoagulation is the most frequent cause for recurrent LVO.